Otomatisasi Pakan Kucing Berbasis Mikrokontroller Intel Galileo Dengan Interface Android - Samsugi, S.; Neneng, N; Suprapto, Galih Naufal Falikh (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
To raise cats, feeding is one of the main factors and should be given according to schedule. If the direct feed with a large portion can result in the cat not being eaten because it is not too deep to eat and is wasted. As a result of this problem, anxiety arises from the point of view of the health and development of cats and leads to spending on excess cat feed. The results of this study are a tool that can help feed cats in real time with 2 modes of feeding, namely for adult cats and kittens with feeding schedules at 8 AM, 12 PM and 6 PM. Control of this tool can be accessed wirelessly with an Android smartphone so that it can make it easier to monitor the working status of this tool. The benefits obtained from the results of making this tool when viewed from the cat are able to maintain their diet, prevent malnutrition, prevent obesity and prevent cats stress due to deposition. When viewed from the point of view of the benefits to cat owners or users, namely it can reduce performance and minimize forgetting to feed and can save on buying cat feed because portions have been arranged in such a way as to save expenditure..